Cyclicality of labour market search: a new big data approach - Christian Hutter (Journal for Labour Market Research, 2021)
This paper exploits big data on online activity from the job exchange of the German Federal Employment Agency and its internal placement-software to generate measures for search activity of employers and job seekers and-as a novel feature-for placement activity of employment agencies. In addition, the average search perimeter in the job seekers' search profiles can be measured. The data are used to estimate the behaviour of the search and placement activities during the business and labour market cycle and their seasonal patterns. The results show that the search activities of firms and employment agencies are procyclical. By contrast, job seekers' search intensity shows a countercyclical pattern, at least before the COVID-19 crisis.
Keywords: C55; J61; J64; 330; Big data; Labour market search intensity; Placement activity; Cyclicality